Cathepsins and cancer risk: a Mendelian randomization study - Deng, Tingting; Lu, Xixue; Jia, Xuemin; Du, Jinxin; Wang, Lijuan; Cao, Baorui; Yang, Meina; Yin, Ying; Liu, Fanjie (Frontiers in Endocrinology, 2024)
Background: Previous observational epidemiological studies reported an association between cathepsins and cancer, however, a causal relationship is uncertain. This study evaluated the causal relationship between cathepsins and cancer using Mendelian randomization (MR) analysis.We used publicly available genome-wide association study (GWAS) data for bidirectional MR analysis. Inverse variance weighting (IVW) was used as the primary MR method of MR analysis.After correction for the False Discovery Rate (FDR), two cathepsins were found to be significantly associated with cancer risk: cathepsin H (CTSH) levels increased the risk of lung cancer (OR = 1.070, 95% CI = 1.027-1.114, P = 0.001, PFDR = 0.009), and CTSH levels decreased the risk of basal cell carcinoma (OR = 0.947, 95% CI = 0.919-0.975, P = 0.0002, PFDR = 0.002). In addition, there was no statistically significant effect of the 20 cancers on the nine cathepsins. Some unadjusted low P-value phenotypes are worth mentioning, including a positive correlation between cathepsin O (CTSO) and breast cancer (OR = 1.012, 95% CI = 1.001-1.025, P = 0.041), cathepsin S (CTSS) and pharyngeal cancer (OR = 1.017, 95% CI = 1.001-1.034, P = 0.043), and CTSS and endometrial cancer (OR = 1.055, 95% CI = 1.012-1.101, P = 0.012); and there was a negative correlation between cathepsin Z and ovarian cancer (CTSZ) (OR = 0.970, 95% CI = 0.949-0.991, P = 0.006), CTSS and prostate cancer (OR = 0.947, 95% CI = 0.902-0.944, P = 0.028), and cathepsin E (CTSE) and pancreatic cancer (OR = 0.963, 95% CI = 0.938-0.990, P = 0.006).Our MR analyses showed a causal relationship between cathepsins and cancers and may help provide new insights for further mechanistic and clinical studies of cathepsin-mediated cancer.